Melatih Konsentrasi Melalui Permainan Sensorimotor pada Anak Kelompok A dalam Pembelajaran Masa Kenormalan Baru di RA Muslimat NU 10 Banin Banat Gresik - Fadlilatur Rohmah; Mukhoiyaroh; Hernik Farisia (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
The background of this research is that there are students who have difficulty concentrating when learning the new normal period in class A1 RA Muslimat NU 10 Banin-Banat Gresik. The purpose of this study was to describe the application of sensorimotor play used to train concentration and to find out the supporting and inhibiting factors for the application of sensorimotor play used to train concentration. This research uses qualitative research with a case study approach. The results showed that the teacher of class A1 applied auditory sensorimotor play using pop up story books at the beginning of the lesson and at the end of the lesson. In addition, the teacher also applies a proprioceptive sensorimotor play using lego and bombic which are usually done during the safety corner, when the child has completed all his tasks. Factors that support the application of sensorimotor play to train children's concentration are the availability of media, increase children's insight, increase children's vocabulary, develop aspects of children's social emotional development, while the inhibiting factors are difficulties in conditioning students, the amount or quantity of media that is lacking.